2005
DOI: 10.1063/1.2105999
|View full text |Cite
|
Sign up to set email alerts
|

Near-field scanning optical microscopic transient lens for carrier dynamics study in InGaN∕GaN

Abstract: Time-resolved microscopic transient lens ͑TR-M-TL͒ and near-field scanning optical microscopic transient lens ͑NSOM-TL͒ were performed to reveal temporal and spatial behavior of carrier dynamics in InGaN/ GaN quantum wells. The carrier and thermal dynamics were observed through the time profile of the TR-M-TL signal. Also, NSOM-photoluminescence and NSOM-TL images were observed at the same time. By comparing these two images, both radiative and nonradiative recombination centers in InGaN active layer were unam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Electroluminescence and photoluminescence ͑PL͒ SNOM studies of c-plane InGaN QWs have identified carrier localization and nonradiative recombination centers, [7][8][9] and revealed potential barriers around the extended defects. Scanning near field optical microscopy ͑SNOM͒, which provides subwavelength spatial resolution, is a more powerful technique for characterizing the carrier localization.…”
mentioning
confidence: 99%
“…Electroluminescence and photoluminescence ͑PL͒ SNOM studies of c-plane InGaN QWs have identified carrier localization and nonradiative recombination centers, [7][8][9] and revealed potential barriers around the extended defects. Scanning near field optical microscopy ͑SNOM͒, which provides subwavelength spatial resolution, is a more powerful technique for characterizing the carrier localization.…”
mentioning
confidence: 99%
“…The lateral sizes of In-rich area are reported in a wide range from a few nm to hundreds of nm and they form a sort of Inrich quantum disks (Q-disks) or quantum dots (Q-dots) [13,14]. The volume of Q-disks (or Q-dots) are much smaller than the physical volume of a QW, namely V eff << V a .…”
Section: Carier Density N [Cmmentioning
confidence: 98%
“…Lots of experimental evidences have suggested the existence of In-rich areas in the active layer of the InGaN-based blue LED, which can act as localization centers of carriers and behave more like quantum disks (Q-disks) or quantum dots (Q-dots) with reduced density of states [13][14]. The existence of In-rich areas implies that the effective active volume is smaller than the nominal volume of QWs.…”
Section: Introductionmentioning
confidence: 99%
“…NSOM is not only used to optically study the surface morphology, but has been successfully integrated with different spectroscopy techniques such as Raman (TERS) [3,4], photoluminescence [5], time resolved measurements [6], etc. It has been used to study a variety of materials, such as solid state quantum nanostructures [7,8], single molecules [9] or soft biological tissues [10,11].…”
Section: Introductionmentioning
confidence: 99%